Lead like it matters ... because it does : practical leadership tools to inspire and engage your people and create great results! - Bahar Hewertson, Roxi (McGraw Hill-Ascent Audio, 2014)
Whether you're a manager, executive, or CEO, leadership matters. Whether you're running a large global firm or a small project team, it's the way you communicate and connect to other people that can make or break your success. The secret, according to Roxi Bahar Hewertson, is to make those connections count--to leverage your skills and play on your strengths--to lead like it matters...because it does. A virtual crash course in leadership, Lead Like ItMatters...Because It Does combines three decades of experience and research with Hewertson's revolutionarywork at Cornell to create the definitive workbook. Learn how to: Assess your leadership style and skill set--and make adjustments Create constructive dialogues including "managing up" and delegation Cut wasteful meetings out of your life and lead productive ones Address common interpersonal conflicts, quickly and gracefully Increase productivity, team effectiveness, and accountability Lead change initiatives that aren't dead on arrival, but ready for takeoff As an executive coach, Hewertson knows how to pinpoint the problems, pressures, and pain points that plague managers at every level--and shows you how to fix them. You'll discover the "ripple effect" that negative leadership choices can have throughout an organization--and how to make positive ripples with clear intent and powerful impact. You'll find a wealth of practical, user-ready tips for handling conflicts, reducing turnover,making confident decisions, and instituting changes in the workplace. This book is packed with handy charts, helpful questionnaires, step-by-step checklists, and other must-haves--it's your own personal toolbox of field-tested techniques, right at your fingertips. Take charge of your future. Build the best team you can. Make changes that count. Lead Like It Matters...Because It Does.